2021
DOI: 10.1108/ijcma-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and health-care worker's combating approach: an exhausting job demand to satisfy

Abstract: Purpose This study aims to investigate the relationship between person-role conflict, psychological capital and emotional exhaustion. Specifically, the research explores how person-role conflict magnified due to daily contact with COVID-19 carriers leads doctors and nurses to experience emotional exhaustion. Moreover, psychological capital function as an explanatory mechanism between stressor strain relationships has also been tested. Design/methodology/approach The study results are based on three months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The loss of people's psychological resources is an apparent result of the COVID-19 pandemic [30,31]. Several studies already have examined employee well-being in the COVID-19 context [32][33][34][35] as an outcome of different resources. COR-driven studies have examined, e.g., survivors' COVID-19-related stress and performance [36], fear of COVID-19 with regard to employees' job insecurity and emotional exhaustion [32], perceived stress and psychological wellbeing [37], and turnover intentions [31].…”
Section: Theory and Hypotheses Development 21 Conservation Of Resourcesmentioning
confidence: 99%
“…The loss of people's psychological resources is an apparent result of the COVID-19 pandemic [30,31]. Several studies already have examined employee well-being in the COVID-19 context [32][33][34][35] as an outcome of different resources. COR-driven studies have examined, e.g., survivors' COVID-19-related stress and performance [36], fear of COVID-19 with regard to employees' job insecurity and emotional exhaustion [32], perceived stress and psychological wellbeing [37], and turnover intentions [31].…”
Section: Theory and Hypotheses Development 21 Conservation Of Resourcesmentioning
confidence: 99%
“…Approximately a month after the diagnosis of the first COVID-19 case in Pakistan, a frontline healthcare professional reported that healthcare workers would not be able to protect themselves and their families from the unprecedented threat posed by the virus (Shah and Huang, 2021). Given the challenges associated with limited resources (i.e.…”
Section: Introductionmentioning
confidence: 99%